THE EFFECTIVENESS OF COURSE REVIEW HORAY LEARNING MODEL WITH ADOBE FLASH ASSISTANCE TO SEE INTERESTS AAD ABILITIES - Chilmi, Fina Idamatul; Sina, Ibnu; Utami, Wikan Budi (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
Aim of this research to describe: 1) There are difference between math learning stake and ability solution to math problem which taught by Course Review Horay method Adobe Flashes aided, 2) Math learning stake and ability solution to math problem which taught by Course Review Horay method Adobe Flashes aided better than only Course Review Horay method. Data analysis technique that used are Right Side Proportion Test, T-tes One Right Side, Manova Test, and ?^2- Hotelling. Result of this research are: 1) There are difference between math learning stake and ability solution to math problem which taught by Course Review Horay method Adobe Flashes aided with only Course Review Horay method, 2) Math learning stake and ability solution to math problem which taught by Course Review Horay method Adobe Flashes aided better than only Course Review Horay method.